A Narrative Review of Multifactorial Determinants of Childhood Eating Behaviors: Insights and Interventions Using the Social Ecological Model - Qutaibah Oudat; Sarah E. Messiah; Alia Dawlat Ghoneum; Anas Okour (Children)
Background/Objectives: Childhood eating behaviors result from a complex interplay of familial, social, and environmental factors, influenced by socioeconomic and cultural contexts. These behaviors impact dietary habits, nutritional status, and long-term health. Using the Social Ecological Model (SEM), this narrative review synthesizes evidence on key determinants of childhood eating behaviors and proposes a framework for multi-level interventions. Methods: A structured literature search was conducted across PubMed, PsycINFO, and CINAHL, focusing on studies published between January 2014 and September 2024. Keywords related to childhood eating behaviors, familial determinants, and social influences were used to identify relevant studies. Inclusion criteria centered on empirical research examining how social and familial factors impact childhood eating behaviors within the SEM framework. Results: The review highlights critical determinants, including parental feeding practices, home food environments, peer influences, screen time, school meal programs, and socioeconomic disparities. These factors interact across multiple levels, emphasizing the importance of holistic interventions that target both individual behaviors and broader systemic influences. Conclusions: Addressing childhood eating behaviors requires a multi-level approach that integrates caregiver education, peer-led interventions, improved food environments, and supportive policies. Healthcare providers and policymakers play a crucial role in implementing strategies that foster healthier dietary behaviors and mitigate childhood obesity risks.